1999
DOI: 10.1046/j.1365-246x.1999.00845.x
|View full text |Cite
|
Sign up to set email alerts
|

Teleseismic shear wave splitting measurements in noisyenvironments

Abstract: High noise levels hamper teleseismic shear wave splitting measurements, which bandpass filtering does not always help. To investigate how robust splitting measurements are to noise, we analysed a set of synthetic records with known splitting parameters and added fixed levels of noise. In the presence of weak anisotropy, single‐waveform splitting measurements are unreliable when operating with noisy data sets. A practical rule in terms of S/N ratio and splitting delay time parameters is that splitting is confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 15 publications
4
68
0
Order By: Relevance
“…However, more often in the noisy environment of Scotland, this resulted in splitting parameters with large associated errors (≥0.5 s in δ t, ≥20° in ϕ) for individual earthquakes. We instead carry out our analysis on un‐filtered seismograms and adopt the stacking procedure of Restivo and Helffrich [1999]. In the stacking procedure, high signal‐to‐noise ratio measurements are given more weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, more often in the noisy environment of Scotland, this resulted in splitting parameters with large associated errors (≥0.5 s in δ t, ≥20° in ϕ) for individual earthquakes. We instead carry out our analysis on un‐filtered seismograms and adopt the stacking procedure of Restivo and Helffrich [1999]. In the stacking procedure, high signal‐to‐noise ratio measurements are given more weight.…”
Section: Discussionmentioning
confidence: 99%
“…Our aim is to constrain better the spatial and temporal origins of anisotropy beneath the area. Existing studies of shear wave splitting in the British Isles suggest that splitting parameters correlate strongly with tectonic features of Caledonian and Variscan age [ Helffrich , 1995; Restivo and Helffrich , 1999]. However, tectonic activity associated with the opening of the Atlantic and emplacement of the British Tertiary Igneous Province (BTIP) at ∼50–60 Ma, may still be affecting deeper structures beneath the Atlantic's passive margins [e.g., Arrowsmith et al , 2005; Ucisik et al , 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Restivo and Helffrich () found that SC anisotropy measurements with SNR > 8 were valid for any back azimuth polarization, whereas measurements with 4 < SNR < 8 were only reliable for waves with back azimuths >20° from the fast splitting direction. Over 94% of all measurements had SNR > 4 for both methods.…”
Section: Methodsmentioning
confidence: 99%
“…However, other methods of obtaining average splitting parameters for a given station that rely on stacking procedures have also been developed. For example, Wolfe and Silver (1998) proposed a method of stacking error surfaces obtained from splitting measurements for phases measured at a variety of backazimuths; a similar stacking technique has been proposed by Restivo and Helffrich (1999). Such stacking methods have the advantage of compensating for noisy data or poor waveform clarity, and making explicit use of null observations.…”
Section: The Transverse Component Minimization Methodsmentioning
confidence: 99%